DESCRIPTION OF URIC ACID LEVELS IN OLDER PEOPLE WHO FREQUENTLY ENGAGE IN SEWING ACTIVITIES IN TILONGKABILA DISTRICT, BONE BOLANGO REGENCY (Journal of Health, Technology and Science (JHTS), 2025)
Older people are a group at increased risk of elevated uric acid levels due to decreased kidney function, metabolic changes, and lifestyle factors such as a high-purine diet and low physical activity. Prolonged sewing activities performed in a static sitting position can slow the body's metabolism and lead to uric acid accumulation, thereby increasing the risk of hyperuricemia. This study aims to identify the profile of uric acid levels in older people who frequently engage in sewing activities in Tilongkabila District, Bone Bolango Regency. The research used a quantitative, descriptive, cross-sectional study design. Uric acid levels were examined using Point-of-Care Testing (POCT). This method uses strips and biosensor devices to detect the oxidation of uric acid in capillary blood samples, providing rapid results with minimal blood volume.  Based on the research results and data analysis, it can be concluded that most elderly respondents in Tilongkabila District, Bone Bolango Regency, who engaged in sewing activities showed abnormal uric acid levels (73.3%), with an average of 7.297 mg/dL
Keywords: Uric Acid, Elderly, Sewing